Role of NPCR and UACI tests in security problems of chaos based image encryption algorithms and possible solution proposals - Özkaynak, Fatih (Institute of Electrical and Electronics Engineers Inc., 2017)
Although chaos based cryptology studies are an active research area, it does not make a significant contribution to the mainstream cryptology literature. Many design proposals have weaknesses. The most important reason is that the proposals are not adequately analyzed. For example, statistical tests such as NPCR and UACI are used in the analysis of chaos based image encryption algorithms. In this study it has been shown that these statistical tests can not be used as a security tool. Therefore, security analysis needs to reevaluate designs made with these statistical tests. A comprehensive analysis road map has been prepared to address this problem. An example of an analysis scenario is shown on a sample image encryption algorithm. The proposed analysis roadmap is intended to fill the lack of analysis in this area. © 2017 IEEE.
Kaos Tabanli Görüntü Şifreleme Algoritmalarinin Güvenlik Sorunlarinda NPCR ve UACI Testlerinin Rolü ve Olasi Çözüm Önerileri
2nd International Conference on Computer Science and Engineering, UBMK 2017 -- 5 October 2017 through 8 October 2017 -- Antalya -- 132116
Keywords: Chaos; Cryptanalysis; Image cipher